Step
*
2
2
1
1
1
1
1
of Lemma
infinitesmal-zero
1. x : ℝ
2. ∀[k:ℕ+]. (|x| ≤ (r1/r(k)))
3. ∀k,n:ℕ+.  ∃N:ℕ+. ∀m:{N...}. (((-2) * m) ≤ (n * ((2 * m) - k * |x m|)))
4. n : ℕ+
5. N : ℕ+
6. ∀m:{N...}. (((-2) * m) ≤ (n * ((2 * m) - n * |x m|)))
7. m : {N...}
8. n ≤ m
9. ((-2) * m) ≤ (n * ((2 * m) - n * |x m|))
10. |m * (x n)| ≤ (|n * (x m)| + |(m * (x n)) - n * (x m)|)
⊢ (|n * (x m)| + |(m * (x n)) - n * (x m)|) ≤ (|m| * 8)
BY
{ (D 1 THEN (Unhide THENA Auto) THEN UnfoldTopAb 2 THEN (RWO "2" 0 THENA Auto)) }
1
1. x : ℕ+ ⟶ ℤ
2. ∀n,m:ℕ+.  (|(m * (x n)) - n * (x m)| ≤ ((2 * 1) * (n + m)))
3. ∀[k:ℕ+]. (|x| ≤ (r1/r(k)))
4. ∀k,n:ℕ+.  ∃N:ℕ+. ∀m:{N...}. (((-2) * m) ≤ (n * ((2 * m) - k * |x m|)))
5. n : ℕ+
6. N : ℕ+
7. ∀m:{N...}. (((-2) * m) ≤ (n * ((2 * m) - n * |x m|)))
8. m : {N...}
9. n ≤ m
10. ((-2) * m) ≤ (n * ((2 * m) - n * |x m|))
11. |m * (x n)| ≤ (|n * (x m)| + |(m * (x n)) - n * (x m)|)
⊢ (|n * (x m)| + ((2 * 1) * (n + m))) ≤ (|m| * 8)
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  \mforall{}[k:\mBbbN{}\msupplus{}].  (|x|  \mleq{}  (r1/r(k)))
3.  \mforall{}k,n:\mBbbN{}\msupplus{}.    \mexists{}N:\mBbbN{}\msupplus{}.  \mforall{}m:\{N...\}.  (((-2)  *  m)  \mleq{}  (n  *  ((2  *  m)  -  k  *  |x  m|)))
4.  n  :  \mBbbN{}\msupplus{}
5.  N  :  \mBbbN{}\msupplus{}
6.  \mforall{}m:\{N...\}.  (((-2)  *  m)  \mleq{}  (n  *  ((2  *  m)  -  n  *  |x  m|)))
7.  m  :  \{N...\}
8.  n  \mleq{}  m
9.  ((-2)  *  m)  \mleq{}  (n  *  ((2  *  m)  -  n  *  |x  m|))
10.  |m  *  (x  n)|  \mleq{}  (|n  *  (x  m)|  +  |(m  *  (x  n))  -  n  *  (x  m)|)
\mvdash{}  (|n  *  (x  m)|  +  |(m  *  (x  n))  -  n  *  (x  m)|)  \mleq{}  (|m|  *  8)
By
Latex:
(D  1  THEN  (Unhide  THENA  Auto)  THEN  UnfoldTopAb  2  THEN  (RWO  "2"  0  THENA  Auto))
Home
Index